2017
DOI: 10.3390/rs9050403
|View full text |Cite
|
Sign up to set email alerts
|

Validation of VIIRS AOD through a Comparison with a Sun Photometer and MODIS AODs over Wuhan

Abstract: Visible Infrared Imaging Radiometer Suite (VIIRS) is a next-generation polar-orbiting operational environmental sensor with a capability for global aerosol observations. A comprehensive validation of VIIRS products is significant for improving product quality, assessing environment quality for human life, and studying regional climate change. In this study, three-year (from 1 January 2014 to 31 December 2016) records of VIIRS Intermediate Product (IP) data and Moderate Resolution Imaging Spectroradiometer (MOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 46 publications
4
28
0
Order By: Relevance
“…Besides, obviously in Table 3, the best performance of DT3K AOD retrievals appears at WH with all statistical metrics (R = 0.84-0.86, RMB = 1.06-1.11, MAE = 0.05-0.07 and 59-63% of retrievals within the EE). Similar comparison results at WH were also reported by [28]. Approximately 72% of the DT3K-CE318 AOD matchups fell into the EE with a high R value (0.87) and nearly 7% of the DT3K AOD retrievals (RMB = 1.07) were overestimated [28].…”
Section: Comparison Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…Besides, obviously in Table 3, the best performance of DT3K AOD retrievals appears at WH with all statistical metrics (R = 0.84-0.86, RMB = 1.06-1.11, MAE = 0.05-0.07 and 59-63% of retrievals within the EE). Similar comparison results at WH were also reported by [28]. Approximately 72% of the DT3K-CE318 AOD matchups fell into the EE with a high R value (0.87) and nearly 7% of the DT3K AOD retrievals (RMB = 1.07) were overestimated [28].…”
Section: Comparison Methodssupporting
confidence: 82%
“…Similar comparison results at WH were also reported by [28]. Approximately 72% of the DT3K-CE318 AOD matchups fell into the EE with a high R value (0.87) and nearly 7% of the DT3K AOD retrievals (RMB = 1.07) were overestimated [28]. Figure 3 also reports the comparison results of the DT10K and CE318 AOD retrievals.…”
Section: Comparison Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…Moreover, our group established a Cimel sun photometer CE-318, which is the same equipment used at AERONET sites since 2010. Relationships between sun photometer-derived AODs and MODIS-derived AODs have been established in Beijing [61], Taihu Lake [62], Hong Kong [63], and Wuhan [64], respectively. Through these studies we found that the slopes of the regression equations ranged from 0.8-1.1.…”
Section: Potential Uncertainty Due To the Aod Productsmentioning
confidence: 99%
“…The difference between the annual AOD of the two products varied from 0.01-0.34 in terms of the cities. The key factors dominating such a difference were identified as the surface reflectance, AOD, and cloud optical depth [64]. It is very difficult to draw a universal conclusion on whether MODISderived AODs overestimate or underestimate the AOD because such differences are highly seasonand location-dependent.…”
Section: Potential Of Off-nadir Modesmentioning
confidence: 99%